The implementation process of decentralization of health services: a qualitative perspective from Sudan - Noory, Bandar; Hassanain, Sara; Kassak, Kassem (Frontiers in Public Health, 2024)
Background Health system reform initiatives have increasingly embraced decentralization as a key trend. The implementation process and its outcomes are influenced by a myriad of factors, including economic forces, political dynamics, and ideological factors. Comprehending and carefully examining the implementation phase of decentralization and its consequences to achieve desired outcomes is crucial. Notably, this phase is often considered the weakest aspect of policy reforms, especially in developing countries. Therefore, this study aimed to explore and analyze the implementation phase of decentralization and its implications as essentials for achieving intended goals. The study objectives evolved around examining the entire decentralization as a multifaceted social and political process in Khartoum State, Sudan, from its early stages of decision-making, policy formulation, and implementation process and the influencing contextual factors. Methods This study was an exploratory qualitative study that employed in-depth interviews to gather perspectives of healthcare providers and policymakers, semi-structured observations, and thematic analysis. The study utilized Grindle’s framework for analysis. Findings This study revealed a political nature of decision-making, with a top–down approach to the implementation, which also lacked stakeholder involvement. It showed a lack of transparency, official documentation, and proper handover procedures from the Ministry of Health to the devolved hospitals during the implementation process. A conflict of interest between the federal and the state level was also reported. It is important to note that this process occurred within the context of structural adjustment program (SAP) schemes, which had already empowered the private sector in Sudan. Conclusion This study documented the implementation process of decentralization of health services and its influencing factors. The study recommended reforming the decentralization policy through consultative stakeholder involvement and by implementing a concurrent responsibility paradigm that divides authority between the federal and state levels.